The Integration of Dakwah in Journalism: Peace Journalism - Bakti, Andi Faisal; Lecomte, Isabelle (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2015)
This article discusses the integration of Islam, particularly da’wa, with peace journalism. It argues that Islamic communication is basically peace journalism. Islamic communication consists of tabligh (information), taghyir (social change), khairu ummah (exemplary community), and akhlaq al-karimah (noble behavior, civil society), the purpose of which is to perpetuate conflict sensitivity, constructive conflict, and conflict resolution. Muslim journalists can produce articles about Islam to promote Islamic teachings relevant to universal values, including inclusiveness for humanity values which are inclusive. It is important for Muslims to create a platform for sharing information and religious values that can be discussed by audiences.